Analysis and Prediction of some Histone-derived Antimicrobial Peptides from Toads Duttaphrynus melanostictus and Phyrinoidis asper - Muhammad Dailami; I Made Artika; Mirza Dikari Kusrini (The Journal of Pure and Applied Chemistry Research, 2016)
Antimicrobial peptides in skin secretions of toads is a promising methods to combat a wide spectrum of bacteria. Histone H2A is a type of DNA-binding protein that acts as a precursor for several antimicrobial peptides. In toads (family Bufonidae) buforin I and buforin II are examples of antimicrobial peptides that derived from histone H2A. This study investigated the genetic diversity and phylogenetic analysis and in silico prediction of antimicrobial peptides derived from histone H2A of Duttaphrynus melanostictus and Phyrinoidis asper, which were collected from Bogor Agricultural University’s campus area. A new set of primers (Buf_fwd and Buf_rev) were designed by using PrimerBLAST, to amplify 393 nucleotides of the histone H2A gene that codes 131 amino acids. Haplotype diversity of both species are very low. Phylogenetic analysis shows the sample D. melanostictus and P. asper are separated to each other in two different clades. Several short predicted peptides from histone H2A show a potential as an antimicrobial peptides based on in silico prediction. Psychochemical characteristics and 3D structure of potent antimicrobial peptides are described.